The Principle of Ultimum Remidium as Human Rights Protection in Relation to Sexual Violence Crimes: A Legal Comparison between Indonesia, Malaysia, and Tunisia - Fithri, Beby Suryani; Serimin Pinem; Rafiqi; Souad Ahmed Ezzerouali (Jurnal Suara Hukum, 2025)
The principle of ultimum remedium is one of the principles in legal science that serves as an important foundation in the criminal justice system, placing criminal sanctions as the last resort after non-criminal efforts are deemed ineffective. The application of this principle is closely related to children as both perpetrators and victims of sexual violence, emphasizing a humane approach, restorative justice, and the protection of human rights, with a focus on recovery efforts for victims. This article examines the principle of ultimum remedium in relation to its application in sexual violence crimes in Indonesia, Malaysia, and Tunisia. The study results show that all three countries share a common vision in placing criminal sanctions as a last resort and emphasizing the importance of child protection and restorative justice. However, there are significant differences in regulation and implementation challenges. Indonesia and Malaysia have a more systematic and integrated approach, while Tunisia faces legal and social obstacles in consistently applying this principle. Efforts to strengthen law enforcement capacity and update legislation are urgently needed so that the principle of ultimum remedium can be effectively implemented to achieve comprehensive justice and protection for victims of sexual violence